PENGARUH PEMBERIAN PENGHARGAAN DAN HUKUMAN TERHADAP KINERJA PERSONIL POLRES ENREKANG - Ahmad Muhtar; Abdul Samad; Rosnaini Daga (Program Pasca Sarjana IBK Nitro, 2023)
This study aims to determine and analyze the effect of giving rewards and punishments on improving the performance of Enrekang Police personnel. This study uses a quantitative descriptive method. The population in this study amounted to 81 personnel from the Enrekang Police. The method of determining the sample using a saturated sample technique. The analytical tool in this study uses multiple linear regression analysis. The results of this study found that awarding had a positive and significant effect on the Influence of Giving Rewards and Punishments on the Performance of Enrekang Police Personnel on the performance of Enrekang Police personnel. Polres Enrekang while giving awards and punishments simultaneously affect the performance of Enrekang Police personnel the performance of Enrekang Police personnel.